Efisiensi Saluran Pemasaran Sapi Potong Peternakan Rakyat di Kecamatan Soko Kabupaten Tuban - Aji Kusuma Wardana; Taufik Rizal Dwi Adi Nugroho (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Beef cattle farmers in Soko District are still based on prices from intermediary traders because there is no benchmark price from the government, so farmers have a weak bargaining position. The purpose of this research was to determine the level of marketing efficiency of beef cattle in the marketing channel. The study was conducted in Soko District, Tuban Regency, with 60 respondents consisting of 43 breeders, 14 collectors, and three slaughters. The research was conducted from March to June 2022. A sampling of breeders was carried out by purposive sampling, and snowball sampling was carried out to identify the marketing channels. The analysis was done by identifying marketing channels and functions, analyzing marketing margin, farmer's share, marketing efficiency, and profitability index on each marketing channel. The study results showed that there are two models of marketing channels. The first model is called model A, a marketing channel for cattle, and model B, a marketing channel for beef. The marketing channel for the cattle, channel I Model A, is the most efficient. In contrast, the marketing channel for the meat, channel I Model B, is more efficient than Channel II Model B. Based on farmer's share calculations and marketing efficiency, the four marketing channels are efficient because has a farmer's share value of >50% and marketing efficiency of <5%. Breeders are advised to choose the shortest channel in marketing beef cattle. Beef cattle at a young age can be sold through channels I model A and II model A because these channels are already efficient according to margin analysis, farmer's share, marketing efficiency, and profitability index. For beef cattle with mature ages, breeders can sell directly to slaughters such as channel I model B so that breeders can get maximum profits.